Estudo de Primeiros Princípios de Bundles de Nanotubos de Nitreto de Boro sob Pressão Hidrostática - Coutinho, Samir Silva (2007)
In this work were studied the electronic, vibrations and structural properties of boron nitride nanotube bundles (16,0), (12,0) and (8,0), when submitted to the hydrostatic pressure changes. To study such properties, we used the ab initio method employing density functional theory in the approach of the generalized gradient approximation. All the simulations were performed using of the siesta code. The obtained results showed that the circular cross section of each one of the studied bundles undergoes a deformation (elliptic) when applied pressure reaches the value of P > 1,0 GPa for the bundle (16,0), P > 2,0 GPa for the bundle (12,0) and for values greater then 6,5 GPa for the bundle (8,0). For each pressure interval it was calculated the percent relative volume, cohesive energy, modes of vibrations and the band structures. The analysis of the electronic properties, through the band structures, indicates that the characteristics semiconducting of boron nitride nanotubes is preserved during the pressure increasing.